Competition between pinning produced by extrinsic random point disorder and superconducting thermal fluctuations in oxygen-deficient GdBa2Cu3O x coated conductors - Haberkorn, N.; Guimpel, J.; Suárez, S.; Lee, Jae-Hun; Lee, Hunju; Moon, S. H.; Haberkorn, Néstor; Guimpel, Julio (IOP Publishing, 2019)
Fil: Haberkorn, N. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina; Universidad Nacional de Cuyo; Argentina; Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina